MAIN FORMS OF WORK ON DICTION IN THE PROCESS VOCAL AND CHORAL EDUCATION OF STUDENTS ON MUSIC LESSONS - Ivanchenko, L.V. (Educational Dimension, 2004)
The article deals with the questions of vocal-choral skills, The principles of vocal exercises’ selection, methods of working at vocal exercises are underlined. The article is addressed to the future music teachers.